2002
DOI: 10.1001/jama.287.24.3238
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Positive-Pressure Ventilation for Postextubation Respiratory Distress

Abstract: The addition of NPPV to standard medical therapy does not improve outcome in heterogeneous groups of patients who develop respiratory distress during the first 48 hours after extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
182
4
35

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(225 citation statements)
references
References 25 publications
1
182
4
35
Order By: Relevance
“…71 Notably, the earlier study excluded patients with COPD after the first of 4 years of recruitment, 70 and in the second study too few patients with COPD were available to be analyzed separately. 71 Others have raised concerns that noninvasive positive-pressure ventilation was not optimally applied in either trial.…”
Section: 71mentioning
confidence: 99%
“…71 Notably, the earlier study excluded patients with COPD after the first of 4 years of recruitment, 70 and in the second study too few patients with COPD were available to be analyzed separately. 71 Others have raised concerns that noninvasive positive-pressure ventilation was not optimally applied in either trial.…”
Section: 71mentioning
confidence: 99%
“…Two randomised controlled trials [6,7] involving a heterogenous group of patients found that the use of NIV post-extubation did not reduce the rate of reintubation when compared with standard medical therapy.…”
Section: Prevention Of Post-extubation Failurementioning
confidence: 99%
“…Most of the published studies assessing the use of NIV in acute respiratory failure have relied on oro-nasal or facial masks [6,7,18,19]. Although there are no published studies, to the current authors' knowledge, on the superiority of one method over the other in the obese population, prior experience suggests a better tolerance for nasal masks in the morbidly obese, because these tend to be less claustrophobic.…”
Section: Prevention Of Post-extubation Failure Aa El Solh Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Two RCTs on the use of NIV in the treatment of respiratory failure after extubation did not show benefits from NIV in avoiding re-intubation (72,74). The first trial selected 81 patients with different underlying diseases, and did not find any benefit from NIV in terms of re-intubation, duration of mechanical ventilation and stay, and survival (74).…”
Section: Non-invasive Ventilation In the Management Of Respiratory Famentioning
confidence: 99%